1999
DOI: 10.1002/(sici)1099-0682(199909)1999:9<1497::aid-ejic1497>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal Complexes of the Optically Active Cyclopentadienyl Ligand PinCp*: Crystal Structure of (SRe)-(η5-PinCp*)Re(NO)(PPh3)[CONHCH(CH3)C10H7]

Abstract: The synthesis of (η5‐PinCp*)Re(CO)3 [PinCp* = tetramethyl(pinanyl)cyclopentadienyl] is described. Successive substitution of two CO ligands by NO+ and PPh3 generates a 1:1 diastereomeric mixture of chiral‐at‐metal [(SRe)/(RRe)‐(PinCp*)Re(CO)(NO)(PPh3)]BF4. The diastereomers are converted with sodium methoxide into the derivative “esters” (SRe)/(RRe)‐(PinCp*)Re(COOCH3)(NO)(PPh3), and then with (+)‐(R)‐(1‐naphthylethyl)amine to the “amides” (SRe)/(RRe)‐(PinCp*)Re(NO)(PPh3)[CONHCH(CH3)C10H7] [(SRe)/(RRe) = 1:1]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The pentamethylcyclopentadiene (Cp*) derivative is the most widely used for all of these applications. However, recent reports have shown that complexes bearing substituted cyclopentadienyl ligands exhibit enhanced reactivity and/or selectivity for many transformations. ,,, As such, the development of efficient, general, and high-yielding synthetic routes to [Cp R RhCl 2 ] 2 complexes is of high interest.…”
mentioning
confidence: 82%
“…The pentamethylcyclopentadiene (Cp*) derivative is the most widely used for all of these applications. However, recent reports have shown that complexes bearing substituted cyclopentadienyl ligands exhibit enhanced reactivity and/or selectivity for many transformations. ,,, As such, the development of efficient, general, and high-yielding synthetic routes to [Cp R RhCl 2 ] 2 complexes is of high interest.…”
mentioning
confidence: 82%
“…The chemistry of the {Re(NO)(Cp)(PPh 3 )} + fragment has been comprehensively studied by John Gladysz et al and by some other groups, and the results have been published in more than a hundred papers [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The chlorido ligand of the chiral parent complex [Re(NO)(Cp)(PPh 3 )Cl] can readily be replaced by numerous inorganic and organic ligands.…”
Section: Introductionmentioning
confidence: 99%